Efek Pemberian Jus Paprika Merah (Capsicum annuum L.) Terhadap Kadar Kolesterol Tikus Putih (Rattus norvegicus) Bunting - Larasati, Sasmita Dyah; Mayangsari, Elly; Fatmawati, Fatmawati (-)
ABSTRACTDuring pregnancy, the cholesterol level in pregnant women can increase by 50-60%. This increase has occurred since the second trimester and continue to increase until the third trimester. Continuous increase in cholesterol level can causes cholesterol build up in blood vessels so that il narrows the blood vessels which can causes atherosclerotic. In this increase of cholesterol level can be suppressed by choosing the right foods, one of them is consumption of foods that contain vitamin C. Red Paprika is one of the foods that contain high vitamin C, where vitamin C inhibits the work of HMG Ko-A reduktase which play a role in enzyme in the synthesis of cholesterol. The study aims to determine the effect of red paprika juice administration to cholesterol level of pregnant rat. This study used 24 white rats with randomly divided groups into 4 group, the control group, treatment 1 with a dose of 0.85 cc (95 gr), treatment 2 with a dose of 1.7 cc (1.9 gr), treatment 3 with a dose of 3.4 cc (3.8 gr) per head per day. Cholesterol level obtained in this study were cholesterol obtained on first day and the nineteenth days of pregnancy. The post hoc test result showed P1 p=0.33, P2 p=0.008, P3 p=0.008 paired with the control group. The ANOVA test result showed significant result, p=0.004 (p<0.05). in this study it can be concluded that administration of red paprika juice can reduce the cholesterol level in pregnant rats.